NOMINAL MARKING SYSTEM OF BAHASA MANGGARAI AND ITS INTERRELATION TO NAMING SYSTEM OF ENTITIES: A CULTURAL LINGUISTIC STUDY - Erom, Kletus; Mbete, Aron Meko; Artawa, Ketut; Putra Yadnya, Ida Bagus (e-Journal of Linguistics; Vol. 4. Januari 2010 No. 1)
This study analyzes the cultural imagery of the Manggaraian SpeechCommunities (MSC) in “Nominal Marking System (NMS) of Bahasa Manggaraiand Its Interrelation with Naming Systems of Entity (NSE): A CulturalLinguistic Study”. The result of the analysis is useful for both the academic worldand the life of the society, especially the MSC.The study conducted in Manggarai Regency, Flores, East Nusa TenggaraProvince, is qualitative. The data were obtained through observation, elicitation,interview, documentation study, listening, and note taking. For this reason, a numberof questions were prepared in a written form. The data obtained were analyzedthrough steps of selection, listing, translation, and interpretation of the formallinguistic meaning and cultural imagery of the MSC. The result of the data analysisis informally reported and verbally described.To analyze the data, the Cultural Linguistic Theory was applied andsupported by the structural and the dynamic theories. To know the chance and toinspire the study, a number of previous studies were reviewed. To easily understand,direct, and limit the discussion of the study, a number of basic concepts weredefined.Syntactically and semantically, there are four kinds of nominal markers(NMs) of BM. NMs in the forms of personal pronouns (PP): hau ‘you SG’, hia/hi‘he/she’, meu ‘you-PLUR’, and ise ‘they’ mark proper nouns (PN) as theSubject/Agent or Object/Patient in a clause bearing the meaning of subject or objectposition of a clause and not common nouns (CN). NMs in the forms of de/ di/ disemark the noun (CN/pronoun or PN) as the possessor of the possessed noun in aclause bearing the meaning of possession. NMs in the forms of le/ li/ lise mark thenoun (CN/pronoun or PN) as the agent diathesis of an action targeted to a noun asthe patient diathesis in a clause bearing the meaning of addition or the target/localityof an action. And NMs in the forms of ge/ gi/ gise mark the noun (CN/pronoun orPN) added to another noun or become the target/locality of an action taking place ina clause bearing the meaning of addition or the target/locality of an action.Beside the four meanings above, NMS of BM also bears a number of themeanings, as stated in the following. The meaning of kinship intimacy is marked bythe PN marking the kinship names. The meanings of individual and grouprepresentations are revealed by the singular PN itself simultaneously by the plural PN. The meaning of priority to a majority group is revealed by the morpheme of theSubject Pronominal Copy fused in one of clause functions (Predicator, Object, andAdverb). The meaning of group of representation is revealed by plural markers onthe singular PN representing other PN that is physically absent from a clause.The NMS of BM has its own phonological and graphological characteristics.Phonology deals with the pronunciation and graphology with the writing of the NMand the noun marked in a clause.The four NMs are grouped into two on the basis of the noun marked, i.e.Common Nominal Markers (CNM), covering de, le, and ge and Proper NominalMarkers (PNM), covering NM in the forms of PP, PNM of possessive di/ dise, PNMof agent diathesis li/ lise, and PNM of combined/targeted gi/ gise. The four PNMsare also grouped into two based on the number of the proper noun (PN) marked, i.ethe singular PNM: hau, hia/ hi, di, li, gi, and the plural PNM: meu, ise, dise, lise,gise.Other linguistic facts in BM seem to appear, such as the common syntacticpattern of BM: Predicator (V) – Object/Patient (N) – Subject/Agent (N), SubjectPronominal Copy, Possessive Pronominal Copy, and nominal repetitions meaningplural in BM are not found.The NSE is given to entities humans, domestic animals: dogs and horses,static objects made by human: cleave and whip, and objects of natural environment:rocks, trees, water sources, and wild animals. The MSC has four kinds of names, i.e.Manggaraian Names (MN), Catholic/Christian Names, Kinship Term Names, andPseudonyms. The interrelation between the NMS and the NSE bears a number ofcultural imageries: differentiation, animacy, honorific, solidarity, identity, prestige,democracy, and work. Initial consonant, especially in proper names, is consideredimpolite, cruel, strong, energetic, while initial vowels polite or gentle.The NMS of BM has undergone significant changed. The change has onlyoccurred on the lexicons, such as changing from BM to BI, even English. The NSEof the MSC has changed significantly. The MN has changed its phonologicalcharacteristics, the number of unit names, the tendency of the children’s namesfollowing their fathers’ names, the decrease in assonance practice in proper namesand some pseudonyms, naming of dogs is not only based on the colour of their fur,the declination of the practice of naming a cleave and a whip, and the PN of theobjects of the natural environment.
Keywords: Bahasa Manggarai, common noun, cultural linguistics, dynamics, imagery, interrelation, marking system, naming system, nominal marker, noun, proper noun.